Linguistic Relativity in SLA: Thinking for Speaking - Hiromi Noguchi (Working Papers in Applied Linguistics and TESOL, 2015)
Over the past few decades, Second Language Acquisition (SLA) research has shown a growing interest in linguistic relativity, specifically in Slobin’s (1987, 1996) thinking-for-speaking hypothesis. The thinking-for-speaking hypothesis posits that language-specific structures direct the speaker’s attention to specific aspects of objects and events; such perceived information is then organized according to what can be grammatically coded in the speaker’s first language (L1s). This volume probes a possible interference of L1-based cognition with second language (L2) development. As pointed out by ZhaoHong Han, the first editor, this volume regards Slobin’s thinking-for-speaking hypothesis as one of the several promising accounts for such SLA phenomena as inter- and intra- learner variability, as well as fossilization.